Analysis of the properties of orthotropic composites in terms of their use in airframe repairs - Arkuszyńska, Angelika; Godzimirski, Jan; Rośkowicz, Marek (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2023)
The aim of the research was to determine the basic strength properties of orthotropic composites in terms of their use in the repair of aircraft airframes. The objects of the tests were three types of composites reinforced with carbon fibers: produced using the wet method with a thickness of 2.5 mm, commercial with a thickness of 2 mm and commercial with a thickness of 7.3 mm. Specimens cut out from the first two types of materials were subjected to a static tensile test with a force applied in the direction of the fibers and at an angle of 45°, which enabled the determination of tensile strength and modulus of elasticity. Specimens made of 7.3 mm thick composite were subjected to four-point bending and tensile tests to determine Young’s modulus, compression and impact strength, also taking into account two directions of load application. The values of stresses and Young’s modulus determined in this way indicate much lower strength and stiffness of orthotropic composites apart from the reinforcement fibers’ directions, which is the basis for replacing them with quasi-isotropic composites in repairs of aircraft airframes.